2017
DOI: 10.1111/desc.12548
|View full text |Cite
|
Sign up to set email alerts
|

Learning across languages: bilingual experience supports dual language statistical word segmentation

Abstract: Bilingual acquisition presents learning challenges beyond those found in monolingual environments, including the need to segment speech in two languages. Infants may use statistical cues, such as syllable-level transitional probabilities, to segment words from fluent speech. In the present study we assessed monolingual and bilingual 14-month-olds' abilities to segment two artificial languages using transitional probability cues. In Experiment 1, monolingual infants successfully segmented the speech streams whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 61 publications
7
66
3
Order By: Relevance
“…However, when provided with a contextual cue of a change in speaker gender, monolingual infants were also able to learn both rules. In a statistical word segmentation task akin to the current study, 14-month-old monolinguals failed to segment two speech streams, whereas bilinguals succeeded (Antovich & Graf Estes, 2018). This study was different from ours in several ways: infants were somewhat older, the speech streams were congruent and presented in alternating blocks during training, speaker gender was used as a contextual cue, and infants were tested on words versus partwords.…”
Section: G Ener Al Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, when provided with a contextual cue of a change in speaker gender, monolingual infants were also able to learn both rules. In a statistical word segmentation task akin to the current study, 14-month-old monolinguals failed to segment two speech streams, whereas bilinguals succeeded (Antovich & Graf Estes, 2018). This study was different from ours in several ways: infants were somewhat older, the speech streams were congruent and presented in alternating blocks during training, speaker gender was used as a contextual cue, and infants were tested on words versus partwords.…”
Section: G Ener Al Discussionmentioning
confidence: 78%
“…Some evidence suggests that learning multiple sets of linguistic rules poses a challenge for infant learners, particularly those growing up in monolingual environments (Kovács & Mehler, , ; Potter & Lew‐Williams, ). Most relevant to this study, Antovich and Graf Estes () compared monolingual and bilingual 14‐month‐old infants who were exposed to two congruent speech streams made up of nonoverlapping syllable inventories. The streams were interleaved during familiarization, and additionally, were presented with a contextual cue to separate the speech streams (one stream was spoken by a female and the other by a male).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Antovich & Graf Estes (2017) tested 14-month-old infants in a simulated bilingual exposure task in which two artificial language streams were interleaved. Again, an indexical cue was present to indicate to learners that multiple streams were present.…”
Section: Real-world Problemsmentioning
confidence: 99%
“…Further, a recent study by Antovich and Graf Estes (2017) examined early word segmentation in a bilingual context using artificial languages. They found that while 14month-old monolingual infants could only segment bi-syllabic words in one of two language streams, their bilingual peers were able to segment words from both language streams.…”
Section: Experiments 1: Discussionmentioning
confidence: 99%
“…Recent computational studies suggest that segmentation performance from a bilingual corpus is only slightly disadvantaged, when compared to that from a monolingual corpus (Fibla Reixachs, 2017). Further, behavioral studies using artificial languages suggest that adults and bilingual infants have the capacity to segment different words from two language streams with different properties (Antovich & Graf Estes, 2017;Weiss, Gerfen, & Mitchel, 2009). In fact, bilingual infants show a slight advantage over monolingual infants in these artificial language tasks (Antovich & Graf Estes, 2017; (Nazzi, Mersad, Sundara, Iakimova & Polka, 2014); thus, while bilingual infants are able to show segmentation in both of their native languages in certain testing conditions, these findings indicate that the strategies they use may be different than those of monolingual infants.…”
Section: Word Segmentation In Bilingual Infantsmentioning
confidence: 94%